Analisis Keikutsertaan Mahasiswa dalam Organisasi Guna Menunjang Prestasi Akademik Mahasiswa UNUSIDA - Rizkiyah Alvina Ramandhita; Wahyu Eko Pujianto (Jurnal Publikasi Ilmu Manajemen, 2024)
Higher education is not only a place to acquire academic knowledge, but also an arena for broader self-development. Students' involvement in organizations on campus has a significant impact on the development of non-academic competencies and skills, which in turn can support their academic performance. This study aims to analyze students' participation in organizations to support academic achievement, as well as to analyze the strengths and weaknesses of organizational activities for students of Universitas Nahdlatul Ulama Sidoarjo. The research method used is qualitative by collecting data through observation and in-depth interviews with informants who are active in organizations and lecturers. The results showed that participation in organizations made a positive contribution to students' self-development, improved learning achievement, and developed soft skills that could help them in facing challenges in the academic and professional world.